MEDIA ORIENTALISM: THAILAND QUEER GENDER DEPICTIONS THROUGH THE LENS OF CONTEMPORARY INDONESIAN POPULAR MEDIA - Sandy Allifiansyah; M Fikri Akbar; Nada Arina Romli (Faculty of Social and Political Sciences, Universitas Diponegoro, 2025)
This research aims to examine the orientalism characteristics in contemporary Indonesian popular media contents on Thailand queer gender images. As Indonesian society consume popular contents from various forms, the popular textual ideology definitely conceives the dominant media cognitive which imposes and drives people perspective on various issues, including queer gender from overseas. Popular media contents become the major reference as they’re easy to access, packed in simple languages and sensational. Thailand as the neighboring country has well known by its vibrant queer gender environment. This image has been articulated in the Indonesian popular media for a long time. Nevertheless, as the LGBT moral panic begins to emerge in contemporary Indonesia, the current Thailand queer gender depictions in Indonesian popular media has also shown frivolous tunes and justifications. This study used Van Dijk’s critical discourse analysis to dissect how Edward Said’s concept of Orientalism works in 21st century popular media contents. Examining 76 Indonesian popular media contents as in pop news websites, commercial movies, popular Youtube channels, and prime time variety shows, the research reveals 11 characters of Indonesian media orientalism point of views toward Thailand queer gender images. Notably, the study found 11 media orientalism characters have just emerged in the last 5-6 years, in parallel with the rise of moral panic against LGBT community in contemporary Indonesia.